Importance of the Development Army in the Context of Nepal - Gayawali , Bikash (Unity Journal, 2021)
In the present context of Nepal, moves towards sustainable development, poverty alleviation, and employment generations in the country are the common expectations of all Nepalese people. Some innovative development strategies are essential to materialize the vision “Prosperous Nepal and Happy Nepali”. Development Army can be a novel concept to build up the foundation for sustainable development and upliftment of Nepal from developing country to developed country. In this concept, additional branch of the Nepal Army trained with a specific set of skills will specialize in mega-hydroelectricity generation and transmission, construction of mega-highways and human capital development. The research question of this article is formulated as “Is concept of Development Army viable for instantly responding to the needs of development and prosperity in present context of Nepal?” The major objective of this article is to create a spark in the mind of readers on importance of Development Army to combat major problems like poverty, unemployment, foreign employment and relative inefficiency of bureaucratic and private sectors to bring economic growth and climacteric changes in the country. Due to exploratory nature of the study, eff ort is being made to find new insights on involvement of Nepal Army in development activities with the help of secondary data. The major finding of this article is that the exquisite and valuable Nepal Army has huge potential to contribute in the development of Nepal by designing Development Army. It can be utilized in infrastructure development and skill based human capital development with the help of respective divisions.